KONSTELASI BAHASA JAWA MODERN DALAM PAGELARAN WAYANG KULIT PURWA (KAJIAN SOSIOLINGUISTIK) - Basir, Udjang Pr. M. (Diksi, 2009)
The shadow puppet performance as part of the Javanese folk arts reflects thesociety's life attitude and philosophy. This art is not only a performance, but it is alsoguidance consisting of traditional values and didactic philosophy that the society canemploy. Language is a medium of communication to present the values and essence of thestory in a shadow puppet performance and has an important and strategic function.Through language, shadow puppet characters are made alive by the puppeteer. This studyinvestigates language variants in the shadow puppet performance. There are six types,namely kasar, ngoko, madya, krama, bagongan and renggabasa. Renggabasa is used insulukan, janturan, antawecana, panyandra, and sasmita. The data reveal that theelaboration shows the growth of the Javanese levels more comprehensively.Keywords: shadow puppet performance, guidance, didactic philosophy